Analysis of Financial Performance Comparison Between Islamic Banking and Conventional Banking During Covid-19 and Post-Covid-19 Periods - Lilis Marlina; Dian Urna Fasihat; Rizkiana Iskandar (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study is to compare the financial performance between Islamic banks and conventional banks. This research falls under the category of comparative research with a quantitative approach. The research population includes banks registered with the Financial Services Authority (OJK) during the period 2020-2022. The sample selection method used purposive sampling technique. The data collected in this study will be analyzed using ratios CAR, NPL/NPF, ROA, and BOPO. This research involves two stages of testing, namely descriptive statistical testing and hypothesis testing. The results of the research show that there is no significant difference in the financial performance between Islamic banks and conventional banks.